Pañcāyata Tālīma Adhikārī ra Pañcāyata Tālīma Sahāyakaharūko Vicāra Goshṭhī prativedana, 2032 (Grha Pañcāyata Mantrālaya, Tālīma Sāmagrī Utpādana Kendra, 1975)
Report on a Seminar of the panchayat training officers and workers, organized by the Pañcāyata Vikāsa Praśikshaṇa Kendra, Mujelia, Nepal.